Assessment of dose consequences based on postulated BDBA (beyond design basic accident) A-30MWt RSG-GAS after 30-year operation. (October 2021) - Udiyani, P.M.; Setiawan, M.B.; Subekti, M.; Kuntjoro, S.; Pane, J.S.; Hastuti, E.P.; Susiati, H.
Abstract: An assessment of the consequences of radiation doses due to the BDBA (beyond design basic accident) on the RSG-GAS research reactor has been done. The assessment was carried out to evaluate the KNS (Serpong Nuclear Area) EPZ (emergency preparedness zone) site after the reactor was operational for 30 years. The RSG-GAS research reactor is a 30MWt multipurpose reactor. It is the largest research reactor in Indonesia. RSG-GAS was built in the KNS Area in the Puspiptek complex which was put into operation in 1987. Previous estimations of the radiological consequences were made on accidents which were postulated based on DBA conditions. With the aging of the reactor, a study was carried out on the radiological consequences of the BDBA accident. The ATWS (anticipated transient without scram) event caused the BDBA condition which resulted in the melted of 5 fuel bundles. Source term is estimated based on an inventory of 5 melted fuel bundles, and fission products release through the reactor core, cooling system, reactor hall, and finally discharge to the environment through the reactor stack. Radionuclide inventory is calculated by ORIGEN2.1. With the influence of weather, fission products are dispersed into the air and deposited to the surface of the soil on the site. Weather and environmental data used are spatial analysis of ARC-GIS. Consequences analysis was carried out in 16 wind direction sectors within a 5 km radius using PC-COSYMA. The calculation results show the largest dose is reached in a radius below 500 m with the direction of the wind to the South. The radiation dose is below the dose limits for the exclusion and beyond exclusion area. Consequences of BDBA accident dose at RSG-GAS does not require countermeasure like sheltering, evacuation nor relocation.